Otimização do processo de descelularização renal para obtenção de arcabouço acelular - Destefani, Afrânio Côgo (2018)
Chronic Kidney Disease (CKD) is characterized by progressive deterioration of renal function, which can compromise various tissues and organs. The main therapy indicated for patients with CKD is renal transplantation. However, the absence of available organs, as well as an organ rejection rate, is required for new therapies. Thus, the implementation of bioengineering for organ regeneration has emerged as an alternative to traditional organ transplantation. Currently, overtime has been expended on total renal decellularization by perfusion with detergents. In these cases, there is a loss of essential components of the extracellular matrix (ECM) and derangements in the scaffold architecture obtained which can substantially influence subsequent cell repopulation. In this work, the total discoloration of rat kidneys was measured in reduced time with the use of detergent solution (SDS, 1%) by renal technique under pressure (100 mmHg) and flow (1.0 mL/min). At the end of this stage, the scaffolds were incorporated as translucent physical characteristics and preserved vascular conduits. An electron microscopic and histochemical analysis revealed glomeruli with a preserved basement membrane, as well as a tubular and vascular network with no cell and DNA residues. Proteomic analysis identified the preservation of majority proteins related to ECM compounds. Thus, the use of low concentration of SDS for 6 hours promoted a successful thawing, in addition to preserving a MEC with the minimum residue of SDS (<0,01%). Also, we developed a retraction index as a correction calculation due to elastic retraction of the kidney after processing. Electron microscopy, spectrophotometric quantification, and mass spectrometry analyzes were performed to compare the results. We demonstrated that the histological analysis, easy technique, and low cost, presented excellent results when the correction index was applied, allowing the comparison of samples before and after the process with reliable data. With these data, we demonstrate that it is possible to reduce the time of decellularization with the preservation of essential components of the ECM.